HAM DAN KEBEBASAN BERPENDAPAT DALAM UUD 1945 - Hsb, Mara Ongku (AL WASATH Jurnal Ilmu Hukum, 2021)
Human rights are rights inherent in a person since birth that cannot be contested by anyone because it is a private property and guaranteed by the state to protect every citizen, one of which is freedom of opinion orally or in writing, which is regulated in the Declaration. General Human Rights, in the 1945 Constitution. The purpose of this study is to determine human rights and freedom of opinion in the 1945 Constitution. Research methods library research (literature study), in legal research the method of normative juridical approach or literature law research which means an approach based on legal rules as a provision and also the constitution. The results of this study indicate that the freedom of opinion in the 1945 Constitution regulated in law is the right to express opinions, express thoughts and to form an association (UUD 1945 article 28 E, F), Law No. 39 of 1999 about human rights Articles 14, 23, 24, and 25. Law No. 9 of 1998 emphasizes that freedom of opinion is a fundamental right in life that is guaranteed and protected by the state. lately freedom of opinion is sometimes still reasonable for constructive criticism made by the community but often freedom of opinion experiences a narrowing of public space, both oral and written.